The perceptual system: That little time-machine - Velasco, I; Spence, C; Navarra, J (2011)
Various physical circumstances (for instance, the fact that light and sound do not travel at the same speed) and/or physiological factors (such as the fact that auditory signals are initially processed more rapidly than visual signals) give rise to small asynchronies between sensory signals pertaining to a specific multisensory event. Considering the large amount of sensory stimulation that bombards our senses at any given time, being able to re-group sensory signals that belong to the same event (even if they arrive asynchronously) can be highly adaptative. Indeed, the human brain is by-and-large able to maintain a simultaneous and coherent perception of the proximal events that occur in the environment. How is this achieved? Two recently discovered phenomena -temporal ventriloquism (where the presence of a stimulus in one modality influences the perceived time of occurrence of a stimulus in another modality) and temporal recali-bration (where the brain realigns asynchronous signals from different sensory modalities)- confirm that the way in which the human brain maintains synchrony is more active and flexible than previously thought. © 2011: Servicio de Publicaciones de la Universidad de Murcia.